2007
DOI: 10.1002/j.2161-1882.2007.tb00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Injury, Gender, and Loneliness Among College Students

Abstract: Several studies have demonstrated relationships between loneliness and numerous psychological and physical difficulties among college students. The purpose of this study was to examine whether loneliness might be a factor associated with increased risk of self-injury among college students. The findings did not support the hypothesis that self-injury would be associated with elevated levels of loneliness. The findings were significant but in the opposite direction than expected. Furthermore, the findings regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In addition, the effect of gender was also apparent in age of onset and methods chosen; men started earlier to NSSI than women and chose more serious behaviors like burning and hitting. These results are also consistent with existing studies; the literature demonstrated that men preferred more serious behaviors than women (Andover et al 2010, Dellinger-Ness & Handler 2007, Taylor 2003. Nevertheless, the previous studies performed in Turkey demonstrated a different picture; while a study performed on Turkish high school students showed no gender difference in terms of NSSI (Zoro lu et al 2003), some studies even stated that NSSI was more common among male college students (Toprak et al Although functions of NSSI is a growing body of knowledge, the number of the studies is still limited.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the effect of gender was also apparent in age of onset and methods chosen; men started earlier to NSSI than women and chose more serious behaviors like burning and hitting. These results are also consistent with existing studies; the literature demonstrated that men preferred more serious behaviors than women (Andover et al 2010, Dellinger-Ness & Handler 2007, Taylor 2003. Nevertheless, the previous studies performed in Turkey demonstrated a different picture; while a study performed on Turkish high school students showed no gender difference in terms of NSSI (Zoro lu et al 2003), some studies even stated that NSSI was more common among male college students (Toprak et al Although functions of NSSI is a growing body of knowledge, the number of the studies is still limited.…”
Section: Discussionsupporting
confidence: 91%
“…For example, a meta-analysis of 116 studies found that females were 1.5 times more likely to report NSSI than males, with the largest differences observed in clinical samples (Bresin & Schoenleber, 2015). The method of self-injury also appears to vary according to gender, with methods such as cutting and scratching most commonly reported by females, and self-hitting and burning more typically reported by males (Andover et al, 2010;Dellinger-Ness & Handler, 2007;Klonsky & Muehlenkamp, 2007). Moreover, emerging evidence suggests NSSI may serve different functions for males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness is often associated with various psychological difficulties in adults (Dellinger-Ness and Handler, 2007). Particularly, it might exacerbate some of the difficulties that students face when adjusting to university, perhaps leading some students to feel too tired to learn.…”
Section: Loneliness and Learning Burnoutmentioning
confidence: 99%